Novel Th17 Lymphocyte Populations, Th17.1 and PD1+Th17, are Increased in Takayasu Arteritis, and Both Th17 and Th17.1 Sub-Populations Associate with Active Disease - Singh K; Rathore U; Rai MK; Behera MR; Jain N; Ora M; Bhadauria D; Sharma S; Pande G; Gambhir S; Nath A; Kumar S; et al. (Dove Medical Press, 2022)
Kritika Singh,1,* Upendra Rathore,1,* Mohit Kumar Rai,1 Manas R Behera,2 Neeraj Jain,3 Manish Ora,4 Dharmendra Bhadauria,2 Supriya Sharma,5 Gaurav Pande,6 Sanjay Gambhir,4 Alok Nath,7 Sudeep Kumar,8 Aman Sharma,9 Vikas Agarwal,1 Durga Prasanna Misra1 1Department of Clinical Immunology and Rheumatology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 2Department of Nephrology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 3Department of Radiodiagnosis, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 4Department of Nuclear Medicine, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 5Department of Surgical Gastroenterology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 6Department of Medical Gastroenterology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 7Department of Pulmonary Medicine, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 8Department of Cardiology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, 226014, India; 9Clinical Immunology and Rheumatology Services, Department of Internal Medicine, Postgraduate Institute of Medical Education and Research (PGIMER), Chandigarh, 160012, India*These authors contributed equally to this workCorrespondence: Durga Prasanna Misra, Department of Clinical Immunology and Rheumatology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, 226014, India, Tel +91 5222495273, Fax + 91 522-2668812, Email DurgapMisra@gmail.comPurpose: We evaluated T helper lymphocyte profile, including novel Th17 subsets Th17.1 (secrete IFN-γ, associate with corticosteroid resistance) and PD1+Th17 (secrete TGF-β 1, implicated in fibrosis), and related cytokines in peripheral blood of Takayasu arteritis (TAK).Materials and Methods: We evaluated circulating Th1, Th2, Th17, Th17.1, PD1+CD4+ T lymphocytes, PD1+Th17, and Treg lymphocytes, inflammatory (IFN-γ, IL-4, IL-6, IL-17A, IL-23, IL-1β, TNF-α) and regulatory (IL-10, TGF-β 1) cytokines in peripheral blood of TAK (n = 57; median age 35 (interquartile range 26– 45) years; 40 females) in a cross-sectional design. We studied inflammatory and regulatory cytokines in culture supernatant of peripheral blood mononuclear cells (PBMCs) from TAK following stimulation with anti-CD3/anti-CD28 and their modulation by tacrolimus (immunosuppressive) with/without tadalafil (anti-fibrotic). Furthermore, we followed up immunosuppressive-naïve active TAK (n = 16) and compared T helper lymphocyte populations and cytokines before and after immunosuppressive therapy. Healthy controls (HC, n = 21) and sarcoidosis (disease control, n = 11) were compared against TAK.Results: TAK had higher Th17, Th17.1 and PD1+Th17 lymphocytes than HC (p < 0.001), and higher PD1+CD4+ T lymphocytes than sarcoidosis (p < 0.001). Th17 lymphocytes associated with active TAK after multivariable-adjusted logistic regression (p = 0.008). TAK had greater cytokine secretion from PBMCs (IFN-γ, IL-17A, IL-10 versus HC; IL-6, TNF-α, IL-1β versus HC or sarcoidosis) (p < 0.05). In-vitro, PBMCs from TAK showed reduced secretion of all inflammatory cytokines with tacrolimus, with synergistic reduction in IL-17A, IL-6, IL-1β and IL-10 following addition of tadalafil to tacrolimus. Serial follow-up of immunosuppressive-naïve TAK (n = 16) showed reduction in serum IL-6 and TGF-β 1 (p < 0.05) and IL-6 in culture supernatant (p < 0.05) following immunosuppressive therapy.Conclusion: Novel Th17 sub-populations (Th17.1 and PD1+Th17) are elevated in TAK. Th17 lymphocytes associate with active TAK. In-vitro experiments on cultured PBMCs suggest promise for further evaluation of a combination of immunosuppressive tacrolimus with anti-fibrotic tadalafil (or other anti-fibrotic therapies) in clinical trials of TAK.Keywords: arteritis, aortic arch syndromes, PD-1 protein, drug resistance, corticosteroid, fibrosis